Perfil de conocimiento financiero, género y escolaridad de los padres: evidencia en estudiantes de bachillerato de instituciones del sistema privado - Cabrera Tacuri, Janneth Nohemí (2023)
Financial education is a field that in recent years has been studied with greater emphasis on secondary education, since it is necessary for young people to learn to make sound decisions and to encourage financial inclusion, given this premise, the objective is to evaluate the relationship between financial education, the demographic variable gender and parents' schooling in high school students of private system institutions. The study has a quantitative approach, cross-sectional; deductive and inductive methodology was applied, the information collected is from the data collected from the research project, called: Overview of the use of ICT's for strengthening financial education in "the centennials" of public and private educational institutions in the city of Loja, the survey instrument was used, in which 302 students were analyzed. The main findings of the research reflect that students are at level 4 of financial education, according to the PISA performance level, this means that students are able to apply their understanding of financial terms and concepts, can analyze complex financial products and can also work with a high level of accuracy to solve non-routine financial problems; it is also concluded that there is no relationship between variables, however there are variables that affect financial education, such as: the father's higher education; strategies should be proposed to improve the level of knowledge of the population under study, in order to optimize the financial skills and knowledge of students in the area of personal finance.